PENGARUH QUALITY OF WORK LIFE (QWL) DAN REWARD TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA GURU SEKOLAH DASAR NEGERI (SDN) DI BABELAN BEKASI - Marhamah Marhamah (Jurnal Manajemen Pendidikan, 2014)
The objective of this research is to obtain information about the effect of quality of work life (QWL) and reward on teachers organizational citizenship behavior (OCB). This research used quantitative approach. The research was conducted to all of state elementary schools teachers in the district of Babelan Bekasi by using a survey method with path analysis applied in testing hypothesis. Population in this research were 129 teachers of Estate Elementary School.The research conclude: (1) There is a direct positive effect of quality of work life (QWL) on organizational citizenship behavior (OCB). (2) There is a direct positive effect of reward on organizational citizenship behavior (OCB). (3) There is a direct positive effect of quality of work life (QWL) on reward. Therefore to enhance teachers organizational citizenship behavior can be carried out by quality of work life (QWL) and reward.